Diet Quality in Overweight/Obese Women: Higher Protein Intake During Weight Loss (P08-014-19). (24th October 2019) - Ogilvie, Anna; Shapses, Sue; Schlussel, Yvette
Abstract: Objectives: Accumulating evidence suggests that assessing diet quality rather than nutrients in isolation provides a more accurate representation of the interactions between foods and diseases. The Healthy Eating Index (HEI) is a validated scoring system of diet quality focused on sufficiency of nutritional intake regarding the Dietary Guidelines for Americans wherein lower scores are associated with increased risk of several chronic diseases. The objective of the dietary intervention was to increase protein intake during weight loss in overweight/obese women, and examine dietary quality, as measured by the HEI. Methods: Women (body mass index, BMI, 25–40 kg/m 2 ) were randomly assigned to either high or normal protein groups during a one-year weight loss trial. Food diaries were collected at baseline and multiple times during the intervention. In this secondary outcome, HEI scores were assessed by entering food diary information into the National Cancer Institute's (NCI) Automated Self-Administered 24-hour (ASA24) Dietary Assessment Tool that configures data into 13 food components and calculates HEI in SAS v. 9.4. Results: Forty-one women (58 ± 4.6 years of age with BMI, 32 ±4.5 kg/m 2 ) had a baseline energy intake of 1831 ± 642 kilocalories; 47% of the energy consumed was from carbohydrates, 17% was from protein, and 36% was from fat. Also, HEI was 58.4 ± 15.3. Using standard HEI categories, 29% were in the poor diet quality range (<51), 64% had fair diet quality (51–80), and 7% were in the good diet quality category (>80). Conclusions: Approximately 14% of American adults have poor diet quality (HEI < 51) (cnpp.usda.gov) compared to a larger percentage of women in this study who were consuming a poor diet. Ongoing analysis will determine if HEI changes over time due to weight loss with higher protein intake. Funding Sources: International Life Sciences Institute and NIH-AG-12161 to S.A.S.